Spontaneous resolution of ‘glue ear’ in children- An experience at a tertiary care teaching hospital of Khyber Pakhtunkhwa.: Spontaneous Resolution of Glue Ear in Children - Anwar, Khurshid; Yar Mohammad, Adnan; Khan, Saeed (Pakistan Journal of Health Sciences, 2023)
Otitis media with effusion (OME) is a common cause of treatable hearing impairment in children. As OME is a recurrent problem, a ‘wait and see’ policy is therefore worthwhile before embarking on treating it surgically. Objective: To determine the frequency of cases having spontaneous resolution of otitis media with effusion in the first 3 months after acquiring the disease. Methods: This study was conducted in ENT Department of Hayatabad Medical complex, Peshawar during the period from July 1, 2021 to Sep 3, 2022. Children aging 3-13 years diagnosed with recent onset OME were followed upto 3 months. Children were categorized into two categories; “Resolved” and “Persistent OME” on the basis of pure tone audiometry and tympanometry at the end of 3 months. Using this data, the frequency of spontaneous resolution of otitis media with effusion (glue ear) was calculated. Results: A total of 185 patients were included in the study. The male: female ratio was of 1.28: 1 with mean age of 7.71 ± 2.75years. The 6-9 years comprised 88(47.57%) & was the commonest age group involved by OME and it was in the same group where maximum percentage of spontaneous resolutions of disease occurred. Overall 148(80%) of children with glue ear achieved spontaneous resolution. Statistically this number has been highly significant (p=0.001). Conclusion: OME resolves spontaneously in a significant proportion of children in first 3 months of illness. A close follow up is recommended before embarking on surgery which is best reserved for persisting cases.